2023
DOI: 10.3390/biomedicines11082249
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease: Emerging Therapies and Future Treatment Strategies

Abstract: Inflammatory bowel disease (IBD) is a term used to represent a group of chronic, relapsing inflammatory disorders of the gastrointestinal tract. Crohn’s disease (CD) and ulcerative colitis (UC) are the two major clinical forms. The global incidence and prevalence of IBD have increased over the last 2–4 decades. Despite the specific etiopathogenesis of IBD still being unknown, it is widely recognized that immunological, genetic, and environmental factors are implicated. A greater understanding of the multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Tools like the abovementioned ones represent a step forward in precision medicine. Currently, computational models (CMs), platforms, digital twins, and quantum computers can enable the implementation of such solutions [16,[26][27][28][29][30].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Tools like the abovementioned ones represent a step forward in precision medicine. Currently, computational models (CMs), platforms, digital twins, and quantum computers can enable the implementation of such solutions [16,[26][27][28][29][30].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The review by Bretto et al [ 19 ] (Contribution 3) provides an in-depth examination of the latest developments in IBD therapy, covering both novel biologics and small molecule drugs. This includes advancements in more selective Janus kinase inhibitors, anti-IL-23 antibodies, sphingosine-1-phosphate receptor modulators, anti-integrin therapies, and other small molecules under research.…”
Section: An Overview Of the Published Articlesmentioning
confidence: 99%
“…IBD, encompassing two primary phenotypes, Crohn’s disease (CD) and ulcerative colitis (UC), is a chronic disorder characterized by recurrent inflammation of the gastrointestinal tract ( 102 ). Studies have shown increased levels of succinate in the sera, plasma, and intestinal tissues of IBD patients, along with enhanced expression of SUCNR1 in these tissues ( 65 , 103 , 104 ).…”
Section: Dysregulated Succinate Metabolism and Diseasementioning
confidence: 99%